Late Quaternary fault activity and deformation mechanism in the eastern Tibet Plateau (Dari fault, Bayan Har Block). (20th May 2023) - Liang, Mingjian; Wu, Weiwei; Yang, Yao; Du, Fang; Zhou, Wenying; Zuo, Hong; Liao, Cheng; Liu, Shao; Zhang, Huiping
Abstract: The Dari fault is one of several large NW-trending left-lateral strike-slip faults with Holocene activity inside the Bayan Har Block in the east of the Tibetan Plateau. Through interpretation of high-resolution images, field investigations, and trench excavations, we estimated that the average horizontal slip rate has been 2.6 ± 0.6 mm/y since the late Quaternary. We also identified three earthquake events dated to 15, 609–12, 658 cal BP, 6741–5074 cal BP, and 1947 AD. The large NW-trending strike-slip faults (such as the Awancang fault, Madoi–Gardê fault, Dari fault, and Wudaoliang–Changshagongma fault, which are located in the Bayan Har Block, eastern Tibetan Plateau) all exhibit late Quaternary activity, and appear to have divided the Bayan Har Block into several subblocks. The faults transmit crustal deformation from the interior of the block to the Longriba fault, and the long-term tectonic deformation is converted into vertical uplift in the Longmen Shan region.